An Enhanced Inverter Controller for PV Applications Using the dSPACE Platform - M. A. Hannan; Z. Abd Ghani; A. Mohamed (International Journal of Photoenergy)
This paper presents the simulation modeling and prototype development of an inverter controller for photovoltaic (PV) applications using the dSPACE DS1104 controller platform. The controller platform can link the simulation model developed in the MATLAB/SIMULINK environment to its prototype hardware. In the dSPACE controller, the voltage regulator controls the inverter by employing a proportional integral (PI) controller and the Park transformation method to generate sinusoidal pulse-width modulation (SPWM) signals. The SPWM signals switch the insulated gate bipolar transistor (IGBT) to stabilize the 50-Hz sinusoidal AC output voltages of the inverter. The simulation was performed with a DC power supply that acts as the PV generator to supply the power to the inverter. The simulation model was then translated into the inverter prototype using the dSPACE platform and tested in the laboratory to prove the efficacy of the proposed controller. The experimental results for the inverter system demonstrated the feasibility of the proposed control strategy by maintaining the THD of the output voltage at 4.6%.